THE ROLE OF METHODS AND SKILLS IN TEACHING UZBEK (SCIENCE TIME JOURNAL, 2026)
In this scientific research work, different methods of teaching languages and learning styles were studied and analyzed according to scientific view. Author also pointed her own opinions and tried to illustrate them by examples. The using of bilingual, comparative, communicative methods, kinesthetic, visual learning styles in teaching Uzbek language on this studied issue.